2018
DOI: 10.3126/njc.v2i1.25660
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between Liquid Based Cytology and Conventional Pap Smears at B P Koirala Memorial Cancer Hospital in Bharatpur, Chitwan, Nepal

Abstract: Background and Objective: Liquid based cytology was introduced at B P Koirala Memorial Cancer Hospital in Bharatpur, Chitwan, Nepal, on 29th November 2017. The objective of this study was to compare the results of conventional pap smears over six (6) months periods from 29th May 2017 to 28th November 2017 with the results of liquid based cytology smears over six (6) months periods from 29th November 2017 to 28th May 2018. Methods: This is retrospective study. The results of conventional pap smears over 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…In our daily routine, we observed that the main causes of unsatisfactory samples for conventional cytology are obscuring blood/white blood cells, interfering substances, and cellularity excess. The percentage of unsatisfactory samples we observed for LBC is comparable to the literature [6, 13, 14]. They were higher when comparing to LBC, possibly to the adaptation of the gynecology staff to the new technique when it was implemented.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In our daily routine, we observed that the main causes of unsatisfactory samples for conventional cytology are obscuring blood/white blood cells, interfering substances, and cellularity excess. The percentage of unsatisfactory samples we observed for LBC is comparable to the literature [6, 13, 14]. They were higher when comparing to LBC, possibly to the adaptation of the gynecology staff to the new technique when it was implemented.…”
Section: Resultssupporting
confidence: 85%
“…Pun et al [14] conducted a comparative study between conventional cytology (1,180 samples) and LBC (1,160 samples). The percentage of unsatisfactory samples was lower in the LBC group (1.2 vs. 3.9%), and there was an increase in the detection of epithelial atypia (ASC-US+) when LBC was implemented (3.77 vs. 2.71%).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that LBC had more satisfactory smears when compared to CPS [9,[11][12][13][14][15]. The statistically significant difference between rates of adequacy between two methods was observed elsewhere [8,14,16].…”
Section: Discussionmentioning
confidence: 81%